THE ROLE OF LABORATORY SCIENCE IN NURSING PRACTICE - Savrinov Sodiq Sobirovich; Hakimov Azad Atamuradovich (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract:  Laboratory  science  is  an  indispensable  component  of  modern healthcare, providing critical data for diagnosing, treating, and monitoring diseases. For nurses, understanding laboratory principles and results is essential for patient care, including  early  detection  of  illnesses,  evaluating  treatment  efficacy,  and  educating patients.  This  article  explores  the  significance  of  laboratory  science  in  nursing,  its applications in various clinical settings, and its role in improving patient outcomes.